Exploring the Influence of Motivation and Anxiety on L2 Students’ Learning Outcomes - Zhu, Siying (Transactions on Social Science, Education and Humanities Research, 2024)
In second language studies, motivation and anxiety have always been the focus of scholars at home and abroad. This study conducted a questionnaire survey on over 120 Chinese IELTS candidates and selected 5 participants for case interviews. Relevant analysis was conducted on the results of the questionnaire survey, and the interview data was also summarized, aiming at exploring the relationship between motivation, anxiety, and academic performance in second language acquisition represented by the IELTS exam. The research has shown that there is a significant positive correlation between IELTS scores and the L2 Motivational Self System, with the internal ideal L2 self demonstrating a higher level of impact on scores than the ought-to self. The necessary external motivations have also been proven to be advantageous; There is an overall negative correlation between anxiety and academic performance. The study fills the gap in second language studies for IELTS learning by investigating the current situation of Chinese IELTS candidates. It is suggested that learners should fully utilize the incentive function of L2 motivational self during exam preparation and consciously regulate their anxiety to stabilize their emotional states.